دور التكيف المدرسي في تنمية التحصيل الدراسي لدى تلاميذ المرحلة الابتدائية - Muhamad Zaid, Ismail; Nashaat Abdelaziz, Abdelqader Baioumy (2018)
The primary school is considered one of the second social institution to which the child likes to accept and get acquainted to after acquaintance to the family. It has certain requirements, laws and regulations that required the pupil to achieve the adaptation in order to attain some degree of scholastic success and the integration into the school environment besides the establishment of good healthy relationships. This study aims to identify the role of the schooling adaptation in the development of the educational curriculum among primary school pupils. This is to be done by addressing the previous studies and literatures that are relevant to the research topic that represent all the theoretical literatures that were applicable to the schooling adaptation. The author hence the researcher has applied the descriptive approach and methodology in following up the previous literatures that were relevant to the subject of this research study and discussing the results. The study has recognized that the schooling adaptation has a significant role in the development of the academic achievement among primary school pupils. In addition, the study commends of the necessity for the primary school to include instructional programs and educational plans and to be considered as an integral part of the curriculums in order to help students on the adaptation process towards schools. The study as well recommends the emphasis of the teacher’s role in assisting pupils to be familiar with this adaptation process during the effective training programs throughout and before the service in order to prepare the teacher to deal correctly with the pupil’s psychological problems in their early stages.